Shehu Transform: Extension to Distributions and Measures (Journal of Nonlinear Modeling and Analysis, 2024)
This paper improves the computational aspect of the Shehu transform. An inversion formula is given. Finally the Shehu transform is extended to distributions and measures.
Keywords: Shehu transform; Laplace transform; Integral transform; Distribution; Measure.